ACG Clinical Guideline for the Diagnosis and Management of Gastroesophageal Reflux Disease. (22nd January 2022) - Katz, Philip O.; Dunbar, Kerry B.; Schnoll-Sussman, Felice H.; Greer, Katarina B.; Yadlapati, Rena; Spechler, Stuart Jon
Abstract : Gastroesophageal reflux disease (GERD) continues to be among the most common diseases seen by gastroenterologists, surgeons, and primary care physicians. Our understanding of the varied presentations of GERD, enhancements in diagnostic testing, and approach to patient management have evolved. During this time, scrutiny of proton pump inhibitors (PPIs) has increased considerably. Although PPIs remain the medical treatment of choice for GERD, multiple publications have raised questions about adverse events, raising doubts about the safety of long-term use and increasing concern about overprescribing of PPIs. New data regarding the potential for surgical and endoscopic interventions have emerged. In this new document, we provide updated, evidence-based recommendations and practical guidance for the evaluation and management of GERD, including pharmacologic, lifestyle, surgical, and endoscopic management. The Grading of Recommendations, Assessment, Development, and Evaluation system was used to evaluate the evidence and the strength of recommendations. Key concepts and suggestions that as of this writing do not have sufficient evidence to grade are also provided.